2007
DOI: 10.1002/ppap.200730601
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of N Atoms Through Porous Membranes in Nitrogen Flowing Post Discharges

Abstract: Results of investigations conducted with membranes of several pore diameters are presented: nylon (5 µm), PDVF(1 µm), and polysulfones (1.2 and 3 µm) exposed to a N2 flowing (1 Ln · min−1) microwave (100 W) post discharge, produced at low gas pressure: 130 to 4 000 Pa (1 to 30 Torr). The transmissions of N atoms through these membranes were measured from the intensity variation of the N2, 1st position afterglow before and after the membranes. It appeared that N atoms penetrate and cross the membranes with a tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…Investigations with other membranes also found that T N increased after 30 min of post-discharge from 0.5 to 1 with PDVF (pores 1 m) and from 0.33 to 1 with polysulfones (pores 13 m) [20].…”
Section: Transmission Of N-atoms Through Porous Membranesmentioning
confidence: 79%
See 1 more Smart Citation
“…Investigations with other membranes also found that T N increased after 30 min of post-discharge from 0.5 to 1 with PDVF (pores 1 m) and from 0.33 to 1 with polysulfones (pores 13 m) [20].…”
Section: Transmission Of N-atoms Through Porous Membranesmentioning
confidence: 79%
“…The interaction of N-atoms with nonwoven membranes was investigated on nylon (5 μm) made by cosolvent evaporation from a nylon extruded film and polypropylene (PP) prepared from polypropylene fibers by a melt-blown process, which were exposed as shown in figure 5 to the N 2 flowing (1 slm) microwave (100 Watt) post discharge produced at low gas pressures: from 1 to 30 Torr [19,20,21]. The N atoms transmission through these membranes was measured from the intensity variation of the N 2 (580 nm) afterglow, which results of N atom recombination (reaction (a)), before and after the membranes.…”
Section: Transmission Of N-atoms Through Porous Membranesmentioning
confidence: 99%
“…Transmission of N-atoms through nylon, polyvinylidene fluoride (PDVF), polysulfone, and laboratory made and commercial PP porous membranes was previously reported [2,3] and discussed in terms of variations of the membrane porosity with the treatment time as a result of membrane etching, which is particularly efficient with nylon membranes. The previous results were obtained at a constant N 2 flow rate of 1 Slm.…”
Section: Resultsmentioning
confidence: 98%
“…In previous works, the effect of pore diameter and polymer properties on N transmission through different membranes was evaluated [2,3]. In the present work, we attempt to study the effects of varying the N 2 flow rate and gas pressure of a N 2 flowing microwave post discharge on the N atom transmission through three layered commercial polypropylene (PP) membranes (already used for conventional sterilisation processes) comprising an intermediate layer of fibres with diameters in the range of nanometres.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment by a nitrogen-containing plasma (N 2 , NH 3 ) results, along with etching and polymer radical formation, in insertion of nitrogen atoms into the surface layers of membranes to form N-C bonds [39][40][41][42][43][44][45][46][47][48][49][50][51]. The wettability of membrane surface is therewith improved and their protein adsorptivity is decreased.…”
Section: Treatment Of Polymer Membranes By Plasma Of Inorganic Gasesmentioning
confidence: 99%